2005
DOI: 10.1080/03009740510017922
|View full text |Cite
|
Sign up to set email alerts
|

Knee osteoarthritis and body mass index: a population‐based case–control study

Abstract: A moderate increase in BMI, within the normal weight range, was significantly related to knee osteoarthritis among men. Overweight at any time was related to knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 23 publications
3
61
2
8
Order By: Relevance
“…Of note, while those in the highest BMI categories had a greater risk than those in the lowest categories, no threshold effect was found, which suggests that even modest to moderate levels of overweight-less than conventional definitions of obesity-convey increased risk. Even within the normal weight range of BMI <25 kg/m 2 , moderate increases in BMI have been shown to be significantly related to knee OA [46], which suggests that even modest levels of increasing weight convey an increased risk of knee OA.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, while those in the highest BMI categories had a greater risk than those in the lowest categories, no threshold effect was found, which suggests that even modest to moderate levels of overweight-less than conventional definitions of obesity-convey increased risk. Even within the normal weight range of BMI <25 kg/m 2 , moderate increases in BMI have been shown to be significantly related to knee OA [46], which suggests that even modest levels of increasing weight convey an increased risk of knee OA.…”
Section: Osteoarthritismentioning
confidence: 99%
“…The evidence is strong enough that the American College of Rheumatology OA treatment guidelines recommend weight loss for overweight persons with knee OA [42]. Obesity has been shown to be strongly associated with knee OA across race/ethnicity and sex [43][44][45], although some conflicting evidence about the relative strength of the association in males versus females exists [46]. Analyses conducted on the National Health and Nutrition Examination Survey (NHANES) data show that adults in the United States with a BMI ≥30 kg/m 2 have a >4-fold higher prevalence of radiographic knee OA than those with a BMI <30 kg/m 2 [47].…”
Section: Osteoarthritismentioning
confidence: 99%
“…6,7 Weight, even in the upper tertile of normal range (body mass index (BMI) 22-o25 kg/m 2 ) is associated with an increased risk of developing medial compartment and patellofemoral knee OA, 8,9 suggesting a dose response effect of weight on the incidence of knee OA. Biomechanics may explain part of the contribution of weight to knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…There were no underweight subjects in the present study. Previous studies have also shown that knee OA is more frequent in women and obese people [4,6]. The subjects were classified into five classes of the SD height-weight classification (Table 3).…”
Section: Resultsmentioning
confidence: 99%